Current status, challenges and prospects of antifouling materials for oncology applications - Zhang, Yingfeng; Sun, Congcong (Frontiers in Oncology, 2024)
Targeted therapy has become crucial to modern translational science, offering a remedy to conventional drug delivery challenges. Conventional drug delivery systems encountered challenges related to solubility, prolonged release, and inadequate drug penetration at the target region, such as a tumour. Several formulations, such as liposomes, polymers, and dendrimers, have been successful in advancing to clinical trials with the goal of improving the drug's pharmacokinetics and biodistribution. Various stealth coatings, including hydrophilic polymers such as PEG, chitosan, and polyacrylamides, can form a protective layer over nanoparticles, preventing aggregation, opsonization, and immune system detection. As a result, they are classified under the Generally Recognised as Safe (GRAS) category. Serum, a biological sample, has a complex composition. Nonspecific adsorption of chemicals onto an electrode can lead to fouling, impacting the sensitivity and accuracy of focused diagnostics and therapies. Various anti-fouling materials and procedures have been developed to minimise the impact of fouling on specific diagnoses and therapies, leading to significant advancements in recent decades. This study provides a detailed analysis of current methodologies using surface modifications that leverage the antifouling properties of polymers, peptides, proteins, and cell membranes for advanced targeted diagnostics and therapy in cancer treatment. In conclusion, we examine the significant obstacles encountered by present technologies and the possible avenues for future study and development.